“Green waste” as a substrate component in Begonia spp. potting cultivation - Acosta Durán, Carlos Manuel (2018)
The forest soil is the main substrate in the production of ornamental plants in pots, but its unlimited extraction causes a negative environmental impact. One alternative for replacing the forest soil is the garden waste, also called “green waste”. The aim of this study was to characterize and determine the optimal dose inclusion of green waste in order to use it as substrate component for begonia (Begonia spp.) container cultivation. This experiment was performed in Morelos State, Mexico, in 2015. Physical and chemical laboratory analysis, as well as an agronomic evaluation was performed. Different proportions (100%, 75%, 50%, and 25%) of green waste and forest soil, supplemented by a general substrate (coconut fiber and sawdust, 50/50, v/v) were mixed. A completely randomized design of eight treatments with eight replications was used. Green waste has similar physicochemical characteristics to forest soil. In the growth and development of begonia plants, the results were statistically equal, between treatments of 100% green waste use and forest soil use in six of the sixteen variables studied, and was superior to other treatments, in one of them. As a result of this study, we reached the following conclusion: that green waste is a material that has the necessary physicochemical characteristics for the Begonia spp. container cultivation, and that if its used as a substrate, it could replace the forest soil.